Cutaneous leishmaniasis and conflict in Syria - Al-Salem, W; Pigott, D; Subramaniam, K; Haines, L; Kelly-Hope, L; Molyneux, D; Hay, S; Acosta-Serrano, A (Centers for Disease Control and Prevention, 2016)
War, infection, and disease have always made intimate bedfellows, with disease recrudescence characterizing most conflict zones (1). Recently, increasing violence from civil war and terrorist activity in the Middle East has caused the largest human displacement in decades. A neglected consequence of this tragedy has been the reemergence of a cutaneous leishmaniasis epidemic.